Manufacturer-Dealer Relationships. The Influence of Trust and Commitment to Technological Interface Adoption (2013)
The steep increase in the number and variety of exchange relations, the increased complexity and uncertainty of the business environment cannot be managed without the presence of interpersonal and/or interorganizational trust and relationship commitment. Manufacturer firms have to pay close attention to developing and maintaining relationship commitment and dealers’ trust. The value of such efforts is the most apparent when high levels of competition threaten market shares and the stability of the dealers’ network. This empirical study shows that trust and relationship commitment are important assets for the technological interface adoption and bring significant savings for the manufacturer and dealer.